Annexin A1 in neurological disorders: Neuroprotection and glial modulation - de Souza Ferreira, Luiz Philipe; da Silva, Rafael André [UNESP]; Borges, Pâmela Pacassa; Xavier, Luana Filippi; Scharf, Pablo; Sandri, Silvana; Oliani, Sonia M. [UNESP]; Farsky, Sandra H.P.; Gil, Cristiane D. [UNESP] (Elsevier, 2025)
Neurological disorders, such as neurodegenerative and neuroinflammatory diseases, have contributed significantly to global disability, even considering the rising life years expectations. Therefore, prevention, early diagnosis, and therapeutic alternatives have been essential to avoid the future collapse of health public systems. Annexin A1 (ANXA1), a Ca2 + −dependent protein, is a promising therapeutic candidate for neurological disorders. ANXA1, found in neurons and glia, displays roles in physiological and pathological processes. Despite ANXA1 undoubtedly maintains the blood-brain barrier (BBB) integrity, this review will focus on ANXA1 roles in neurons and glial cells. In neurons, the cytoplasmic expression of ANXA1 is associated with apoptosis, while its nuclear translocation is linked to ischemic neuronal death. Interactions with S100A11, the Tat-NTS peptide, and other molecules, modulate this translocation, suggesting potential therapeutic interventions. ANXA1 expressed on microglia modulates inflammation and efferocytosis. Post-translational modifications, such as SUMOylation, guide the role of ANXA1 in microglia polarization and neuroprotection. In addition, ANXA1 in astrocytes responds to inflammatory stimuli by influencing cytokine release. A comprehensive understanding of the intricate mechanisms of ANXA1 in neurons and glial cells reveals promising therapeutic strategies to alleviate neuronal damage in neurological diseases.
Keywords: Astrocyte; Calcium-dependent phospholipid-binding protein; Microglia; Neurological disorders; Neuron